2013
DOI: 10.1038/nn.3413
|View full text |Cite
|
Sign up to set email alerts
|

A causal link between prediction errors, dopamine neurons and learning

Abstract: Situations where rewards are unexpectedly obtained or withheld represent opportunities for new learning. Often, this learning includes identifying cues that predict reward availability. Unexpected rewards strongly activate midbrain dopamine neurons. This phasic signal is proposed to support learning about antecedent cues by signaling discrepancies between actual and expected outcomes, termed a reward prediction error. However, it is unknown whether dopamine neuron prediction error signaling and cue-reward lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
753
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 815 publications
(817 citation statements)
references
References 43 publications
61
753
1
2
Order By: Relevance
“…This provides behavioural evidence for the importance of prediction errors in learning. As discussed above, more direct evidence has recently been obtained by manipulating phasic dopamine signals (Steinberg et al, 2013) in an appetitive blocking design (Table 2, second row). In a variant of the blocking paradigm (transreinforcer blocking; Table 2, third row; Dickinson and Dearing 1979; Ganesan and Pearce 1988), the identity of the reinforcer is changed in the compound phase, e.g.…”
Section: Outcome Identitymentioning
confidence: 86%
See 4 more Smart Citations
“…This provides behavioural evidence for the importance of prediction errors in learning. As discussed above, more direct evidence has recently been obtained by manipulating phasic dopamine signals (Steinberg et al, 2013) in an appetitive blocking design (Table 2, second row). In a variant of the blocking paradigm (transreinforcer blocking; Table 2, third row; Dickinson and Dearing 1979; Ganesan and Pearce 1988), the identity of the reinforcer is changed in the compound phase, e.g.…”
Section: Outcome Identitymentioning
confidence: 86%
“…Abler et al 2006;Burke et al 2010;Spicer et al 2007;Tobler et al 2007) and more specific predictions of formal learning theories Kahnt et al, 2012;Rutledge et al, 2010;Tobler et al, 2007). However, it is worth keeping in mind that the haemodynamic response measured with neuroimaging is nonspecific rather than a one-to-one reflection of a particular neural event such as dopamine release (see also Düzel et al 2009), which could explain why some fMRI studies have suggested positive coding of losses (Seymour et al 2004; although see also Tom et al 2007) and a dominance of action over value (Guitart-Masip et al, 2012 (Kamin, 1969) used an aversive between-subjects design; by contrast, the experiment described in the text and depicted in abbreviated form here (Waelti et al, 2001) used an appetitive within-subject design where the test consists of a comparison between Y and X (see also Figure 2A); The optogenetic unblocking experiment of Steinberg et al (2013) used a between-subject design.…”
Section: Phasic Dopamine Signals Represent Model-free Prediction Errorsmentioning
confidence: 99%
See 3 more Smart Citations